The Effect of Learning with Approach Teaching at The Right Level Regarding Mathematics Learning Outcomes of Class X Students - Sakniyawati, Wirri; Izzati, Nur; Dwinata, Alona (Journal of Instructional and Development Researches, 2024)
Learning outcomes are defined as students' academic achievements in mastering competency achievement indicators in a material after following the learning process. The results of an initial study at SMA Negeri 4 Tanjungpinang showed that students' mathematics learning outcomes were still relatively low. Implementation of learning with an approach to Teaching at The Right Level (TaRL) is a solution that can be offered to overcome this problem. This research aims to determine the effect of learning with this approach, Teaching at The Right Level (TaRL), on the mathematics learning outcomes of class X students at SMA Negeri 4 Tanjungpinang. The approach used is a quantitative approach. A quasi-experimental with pretest-posttest control group design was applied in this research. The sample for this research was selected randomly through cluster sampling so that class X.4 had 35 students and class X.5 had 32 students as the research sample. Pretest-posttest as a data collection technique. Data were analyzed using an Independent Sample t-test with a significance level of 5%. The research results show an influence of the application of learning with the teaching approach at the right level (TaRL) on student learning outcomes in quadratic equation material in class X SMA.